Forests, human health and well-being in light of climate change and urbanisation - Hägerhäll, C.M.; Ode, A.; Tveit, M.S.; Velarde, M.D.; Colfer, C.J.P.; Sarjala, T. (IUFRO, 2010)
The importance of forests for human health and well-being is well documented in the literature. Forests provide a wide range of ecosystem services beneficial for human life both in urbanised and rural areas, from temperature regulation and air filtration to provision of food and medicinal plants. It is also well documented that forests are important arenas for recreation, aesthetic appreciation and stress relief for people, all of which are of high importance to the health of an increasingly urbanised population. Many of these positive effects that forests have on human health and wellbeing may be altered as a result of climate change and subsequent changes in forest structure and forest cover. The chapter shows that there is reason for concern about the possible changes in human health effects that may come with climate change. In tropical areas, many forest living people who rely heavily on forests in their household economies will be highly vulnerable to forest degradation. Increase in pressure on urban forests and their capacity to provide ecosystem services, reduced availability and quality of recreational areas and higher risk of exposure to vector borne-diseases are some of the effects discussed in this chapter.